Pertumbuhan dan produksi bayam merah (Amaranthus tricolor L.) dengan pemberian pupuk kandang dan giberelin - Dedytha Nur Annisa; Adriani Darmawati; Sumarsono Sumarsono (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2018)
The research aimed to study the growth and yield of red spinach as affected by manures and giberelin. This research used monofactor experiment with Completely Randomized Design consist of 7 treatments and 3 replications. The treatments were T0 (control), T1 (GA3 100 ppm and cow manure 6,250 kg / ha), T2 (GA3 200 ppm and cow manure 12,500 kg / ha), T3 (GA3 300 ppm and cow manure 18,750 kg / ha), T4 (GA3 100 ppm and goat manure 3,750 kg / ha), T5 (GA3 200 ppm and goat manure 7,500 kg / ha), T6 (GA3 300 ppm and goat manure 11.250 kg / ha). Observed parameters were plant height, leaf number, leaf area, wet weight and dry weight. The data were processed by analysis of variance and further test with Duncan Multiple Range Test and Contrast Test. The best plant height growth was in the treatment of 18,750 kg / ha of cow manure and 300 ppm gibberellin resulted plant height of 21.11 cm. The highest number of leaves in the treatment of 11,250 kg / ha of goat manure and 300 ppm gibberellin resulted 21.44 leaves. Leaf area (528.79 cm2), fresh weight (68,50 g), and best dry weight (26.97 g) were achieved at 7,500 kg / ha goat manure treatment and 200 ppm giberelin. It was concluded that the application of manure and gibberellin increased plant growth (plant height, leaf number, leaf area), and crop production (fresh weight and dry weight) of red spinach. The combination of goat manure and giberelin was better than cow manure on all parameters. Goat manure of 7,500 kg / ha and 200 ppm gibberellin increased growth and production of red spinach on leaf area parameters, fresh weight, and dry weight. Keywords : red spinach, manure, gibberellin